Объяснение:
13. y=3x² y=0 x=-3 x=2 S=?
S=₋₃∫²3x²dx=x³ ₋₃|²=2³-(-3)³=8-(-27)=8+27=35.
ответ: S=35 кв.ед.
14. f(x)=x³ x₀=1 yk=?
yk=f(x₀)+f'(x₀)*(x-x₀)
f(1)=1³=1
f'(1)=(x³)'=3x²=3*1²=3*1=3 ⇒
yk=1+3*(x-1)=1+3x-3=3x-2.
ответ: yk=3x-2.
16. Sполн=320π см² Sосев. сеч.=192 см² Vцил.=?
Sполн=2*Sосн.+Sбок=2*πr²+2πrh=2π*(r²+h)=320π
2π*(r²+rh)=320π |÷2π
r²+h=160
Sосев. сеч.=2rh=192
2rh=192 |÷2
rh=96 ⇒
{rh=96 {rh=96 {h=96/r h=96/8=12 (см)
{r²+rh=160 {r²+96=160 {r²=64 r₁=8 (см) r₂=-8 ∉
V цил.=πr²h=π*8²*12=π*64*12=768π≈2412,7 (cм³).
D= 16 - 4(-5) = 36
х1 = (-4+6) / (-10) = -0,2
х2 = (-4 - 6) / (-10) = 1
2) = -21(х + 2/7)(х - 2/6) = - 3*7(х + 2/7)(х - 2/6) =
= - (7х + 2)(3х - 1)
D= 1 - 4(-21)*2 = 169
√D= √169 = 13
х1 = (-1+13 ) / (-42) = - 12/42 = - 2/7
х2 = (-1-13 ) / (-42) = 14/42 = 2/6
3) = -12(х - 1/3)(х - 1/4) = - (3х - 1)(4х - 1)
D= 49 - 4(-12)(-1) = 49 - 48 = 1
х1 = (-7+1) / (-24) = 6/24 = 1/4
х2 = (-7-1) / (-24) = 8/24 = 1/3
4) = 27(х - 1/3)(х + 1/9) = 3*9*(х - 1/3)(х + 1/9) =
= (3х - 1)(9х + 1)
D= 36 - 4*27*(-1) = 36 + 108 = 144
х1 = (6+12) / 54 = 18/54 = 1/3
х2 = (6-12) / 54 = -6/54 = - 1/9